IMPLEMENTASI PAPAN PUZZLE PADA PEMBELAJARAN DENGAN MODEL PEMBELAJARAN MATING DALAM MENINGKATKAN PEMECAHAN MASALAH MATEMATIS SISWA - Puji Rahmawati; Lilian Slow; Yuli Budhiarti (Department of Mathematics Education, Universitas Kuningan, 2022)
This research combines the MATING (Mathematics-English) Learning Model and Puzzle Board Media. The purpose is to develop the MATING learning model by the implementation of puzzle board media in the increasing of students’ problem solving. It conducted in Public Elementary School 01 Semanget and 12 Entikong toward the third-grade student, on March to November. The type of this research is development research with test, observation, and interview in the data collecting techniques. The data analysis technic was analysis-descriptive. Based on the first observation result shows that problem solving competence of both of them is same, it is 25%. Merely there is one problem solving competence on their problem-solving test sheet. Then, researcher conducts the small group tryout in public elementary school 12 Entikong (20 students) and the result shows that there is development in problem-solving competence, it is 50%. It means that there are three steps of problem-solving on their problem-solving test sheet (at the third level). Next, researcher conducts the big group tryout in both of the schools and the result is there are four level of problem-solving on their test sheet (at the fourth level). Thus, there is the increasing is 75% of students’ problem-solving competence. In short, the problem-solving competence can be developed by the combination of MATING learning model and puzzle board media.